The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1073/pnas.94.2.532
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human B-MYB by cyclins

Abstract: B-MYB expression is associated with cell proliferation and recent studies have suggested that it promotes the S phase of mammalian cells. Based on its homology to the transcription factors c-MYB and A-MYB, B-MYB is thought to be involved in transcriptional regulation; however, its activity is not detectable in several cell lines. It was postulated that B-MYB function may depend on the presence of a cofactor, and recent studies suggested that B-MYB is phosphorylated specifically during S phase in murine fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(133 citation statements)
references
References 32 publications
8
122
0
1
Order By: Relevance
“…Also, by focusing on c-Myb and v-Myb, this review has neglected the interactions known for Myb related proteins, which will certainly turn out to be just as varied and complicated as the ones a ecting c-Myb. For example, a lymphoid-speci®c protein has been identi®ed which interacts with A-Myb (Ying et al, 1997), and interactions between B-Myb, cyclin A and cyclin-dependent kinases have been well documented (Lane et al, 1997;Sala et al, 1997;Ziebold et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, by focusing on c-Myb and v-Myb, this review has neglected the interactions known for Myb related proteins, which will certainly turn out to be just as varied and complicated as the ones a ecting c-Myb. For example, a lymphoid-speci®c protein has been identi®ed which interacts with A-Myb (Ying et al, 1997), and interactions between B-Myb, cyclin A and cyclin-dependent kinases have been well documented (Lane et al, 1997;Sala et al, 1997;Ziebold et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Myb-related protein B-Myb has S phase speci®c transactivation activity, and is regulated by cyclindependent kinases (Lane et al, 1997;Sala et al, 1997;Ziebold et al, 1997). Ironically, B-Myb has not been shown to be oncogenic, and no evidence linking c-Myb activity to cell cycle regulation has been reported.…”
Section: C-myb V-myb and Cyclinsmentioning
confidence: 99%
“…Mybs are molecules negatively regulated by their carboxyl-termini, and protein truncation results in activation of the transcriptional activity of both c-Myb and B-Myb (Kalkbrenner et al, 1990;Ziebold et al, 1997;Lane et al, 1997). Several studies have demonstrated that B-Myb is a substrate for the cdk2/cyclinA kinase and that phosphorylated B-Myb is more active, in terms of its transactivating activity, than the unphosphorylated form (Ziebold et al, 1997;Lane et al, 1997;Sala et al, 1997). c-Myb expression is high in the hematopoietic lineages, especially in immature cell types (Gonda and Metcalf, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Although we have yet to examine whether the failure to silence B-myb expression in the brains of B-myb mE2F/mE2F mice (Figure 3f) led to increased apoptosis, neuronal defects were not apparent. B-myb activity is regulated not only at the transcriptional level, but also positively by post-translational modification by cyclin-dependent kinases, in particular cyclin A/cdk2 (Robinson et al, 1996;Lane et al, 1997;Sala et al, 1997;Ziebold et al, 1997). It is likely, therefore, that the B-Myb protein made inappropriately in post-mitotic cells of B-myb mE2F/mE2F mice is not activated, as the cyclin A gene is also an E2F target and would be silenced.…”
Section: Discussionmentioning
confidence: 99%